VIII Hotine-Marussi Symposium on Mathematical Geodesy : Proceedings of the Symposium in Rome, 17-21 June, 2013 /: Proceedings of the Symposium in Rome, 17-21 June, 2013. (2016) - Unknown
No abstract available